THE STRATEGIC IMPORTANCE OF ANTARCTICA FOR CHINA AND INDIA UNDER MEARSHEIMER’S OFFENSIVE REALISM - Portella de Aguiar, Mônica Heinzelmann; Mattos, Leonardo Faria de (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The Antarctic Treaty was signed during the Cold War and intended to preserve the continent and transform it into a conflict free territory, prioritizing scientific cooperation. Despite having quadrupled the number of its signatories, the Antarctic Treaty System (ATS) faces nowadays the uncertainties of the new international order. Starting out from John Mearsheimer’s realistic perspective, this paper aims to analyze, the strategic importance of Antarctica and the interests that China and India have on the continent, as well as speculate on how their rise on the international scenario can impact the future of the Antarctic Treaty System.